(untitled) (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
As a result of the rapid advancement in telecommunication technologies, user demand for higher data transfer speeds is increasing year by year. Today, providing high-speed internet services, accessing cloud computing platforms, and supporting modern applications such as video conferencing and 4K/8K video streaming require a fast and reliable network infrastructure. To meet these demands, Passive Optical Network (PON) technology is recognized as the most promising solution. This chapter provides a detailed examination of the evolutionary history of passive optical networks, the architecture and operating principles of XG-PON technology, the concept and necessity of Dynamic Bandwidth Allocation (DBA), as well as the various types and classifications of existing DBA algorithms.